No Evidence of Systemic Inflammation in Symptomatic Patients With Femoroacetabular Impingement. Issue 10 (18th June 2019) - Talks, Benjamin J.; Fernquest, Scott; Palmer, Antony; Broomfield, John; Pattinson, Kyle; Bradwell, Arthur; Glyn‐Jones, Siôn
ABSTRACT: Femoroacetabular impingement (FAI) is a common cause of hip pain and represents a major cause of early osteoarthritis. The role of systemic inflammation in pre‐arthritic hip conditions remains largely unknown and uninvestigated. Serum‐free light chains (sFLCs) are inflammatory markers produced by B cells. This study aimed to determine whether there was evidence of systemic inflammation in patients with FAI, defined by sFLCs, and whether this correlated with markers of disease severity. Participants for this study were recruited from a single center (Nuffield Orthopedic Center, Oxford) and were taking part in the Femoroacetabular Impingement Trial. The cohort comprised 115 individuals (38 male, 77 female, mean age 37 years): 57 individuals received surgical intervention and 58 received physiotherapy. All individuals provided patient‐reported outcome measures and serum samples at baseline and follow‐up 8 months post‐randomization. sFLC concentrations were measured in serum samples by immunoturbidimetry. At baseline, for all individuals, mean polyclonal sFLC concentrations were 30.36 mg/l (standard deviation [SD] 9.23). At follow‐up, the mean polyclonal sFLC concentrations were 31.68 mg/l (SD 9.61) in the surgical intervention cohort, and 29.48 mg/l (SD 7.85) in the physiotherapy intervention cohort. There was no significant correlation between sFLC concentrations and any of the patient reported outcome measures, or radiographic measures: average or maximum alpha angle, or center edge angle. In conclusion, in patients with symptomatic FAI there was no systemic inflammation, as defined by sFLC concentrations, and no correlation between sFLC concentrations and measures of disease severity. The lack of inflammation suggests FAI is a mechanical phenomenon. © 2019 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 37:2189–2196, 2019